Orbital breathing effects in the computation of x-ray d-ion spectra in solids by ab initio wave-function-based methods. (21st November 2016) - Bogdanov, Nikolay A; Bisogni, Valentina; Kraus, Roberto; Monney, Claude; Zhou, Kejin; Schmitt, Thorsten; Geck, Jochen; Mitrushchenkov, Alexander O; Stoll, Hermann; van den Brink, Jeroen; Hozoi, Liviu
Abstract: In existing theoretical approaches to core-level excitations of transition-metal ions in solids relaxation and polarization effects due to the inner core hole are often ignored or described phenomenologically. Here we set up an ab initio computational scheme that explicitly accounts for such physics in the calculation of x-ray absorption and resonant inelastic x-ray scattering spectra. Good agreement is found with experimental transition-metal L -edge data for the strongly correlated d 9 cuprate Li2 CuO2, for which we determine the absolute scattering intensities. The newly developed methodology opens the way for the investigation of even more complex d n electronic structures of group VI B to VIII B correlated oxide compounds.